Characterization and evaluation of actinomycete from the Protaetia brevitarsis Larva Frass - Zhang, Lida; Zhao, Tianxin; Geng, Lili; Zhang, Chao; Xiang, Wensheng; Zhang, Jie; Wang, Xiangjing; Shu, Changlong (Frontiers in Microbiology, 2024)
Protaetia brevitarsis larvae (PBL) are soil insects important for the soil organic carbon cycle, and PBL frass not only contains a large amount of humic acid but also affects the diversity, novelty, and potential functions of actinomycetes. Here, we characterized and assessed the actinomycete. The operational taxonomic unit (OTU) data showed that 90% of the actinomycetes cannot be annotated to species, and pure culture and genome analysis showed that 35% of the strains had the potential to be new species, indicating the novelty of PBL frass actinomycetes. Additionally, genome annotation showed that many gene clusters related to antifungal, antibacterial and insecticidal compound synthesis were identified, and confrontation culture confirmed the antifungal activities of the actinomycetes against soil-borne plant pathogenic fungi.The incubation experiment results showed that all isolates were able to thrive on media composed of straw powder and alkaline lignin. These results indicated that PBL hindgut-enriched actinomycetes could survive in soil by using the residual lignocellulose organic matter from plant residues, and the antibiotics produced not only give them a competitive advantage among soil microflora but also have a certain inhibitory effect on plant diseases and pests. This study suggests that the application of PBL frass can not only supplement soil humic acid but also potentially affect the soil microbiota of cultivated land, which is beneficial for the healthy growth of crops.The P. brevitarsis population used in this investigation was derived from the wild population in Gongzhuling, Jilin Province, China (Wang et al., 2019). The larvae were raised in a plastic box and kept in an incubator with a relative humidity of 70%, a temperature of 25°C, and a photoperiod of 16 h:8 h. Fully fermented corn straw with approximately 50% moisture content was used to feed the